THE REALITY AND LIMITS OF QUALITY CULTURE - Meryem, Mahdaoui; Abdelghani, Bouchra (The journal of contemporary issues in business and government, 2023)
Continuous improvement, utilization of data and decision-making are essential elements of a quality culture, which encourages the provision of continuous training, development of employees, the use of quality management tools and techniques to analyze data and identify opportunities for improvement. It also encourages personal responsibility and promotes transparency and trust among all members of the organization Accordingly, this study aims to clarify the term quality culture, which represents a comprehensive approach to management and work in organizations, aiming to achieve quality in all aspects of work and operations. It includes principles, values and practices that focus on improving performance, achieving excellence, meeting the needs of customers and partners. Through the study, we concluded that the culture of quality is considered as a basis for achieving excellence and continuity in business and sustainable success in institutions. It is not just a fleeting strategy, but an integrated approach that requires commitment, motivation and evasion of reality, starting from the top leadership to the lowest levels of the organization.